Tony Langlois (ed.), Non-Western Popular Music (2012) - Jones, Jaime (Journal of the Society for Musicology in Ireland, 2014)
A review of Tony Langlois (ed.), Non-Western Popular Music, The Library of Essays on Popular Music 5 (Farnham: Ashgate, 2012). ISBN 978-0-7546-2984-9.